Evaluasi Adverse Drug Reaction pada Pasien Tuberkulosis Anak di Puskesmas Kabupaten Tegal - Bariyah, Fathatul; Karuniawati , Hidayah (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Tuberculosis (TB) is a disease caused by bacteria, namely Mycobacterium tuberculosis (MTB) and needanti-TB drugs (ATD) treatment. The success of ATD therapy is influenced by various factors, including ADRs and their management, which play a role in treatment and retention in care. The frequency and severity of ADRs caused by ATD are always a concern, especially in children. The study aims to determine the prevalence of ADRs, determine the management and outcome of ADR treatment in pediatric TB patients at the Tegal Regency Community Health Center. This study used a cross-sectional design in pediatric TB patients aged 0-18 years. This study showed The most frequent ADRs were gastrointestinal disturbances (16.7%), joint pain (8.3%), peripheral neuropathy (6.7%), and flu-like syndrome (6.7%). The ADR event category is likely to have a percentage of 91% of the overall number of events, followed by the possibility with a percentage of 9% of events. Management strategies, including vitamin B complex supplementation, antacids, multivitamins, probiotics, antipyretics, and topical agents, effectively reduced or eliminated ADRs. The most common ADRs werw gastrointestinal disorders, joint pain and flu syndrome. Management of ADRs related to anti-tuberculosis drugs (ATD) has been successful in reducing or eliminating ADRs. Special attention from healthcare workers should be given to patients at spesific risk groups for ADR management to improve therapy success.